University of Malaya is No. 29 in Asia - Hazlina, Aziz (New Straits Times Press, 2015)
INCREASED VISIBILITY: Malaysia improves its standing in the QS University Rankings Asia 2015 with University of Malaya (UM) breaking into the Top 30, placing it at 29th place from 32 last year